SEPARATION OF MEMBERS OF THE TARIKAT FROM SOCIETY IN SUFISM (A SOCIO-PHILOSOPHICAL ANALYSIS) (Scientific journal of the Fergana State University, 2023)
The article focuses on the fact that Sufism arose as a response to the need for new spiritual needs, intellectual and emotional research at a certain stage in the development of mankind, and that Sufism consoles the hearts of people seeking the truth with its ideas about the spiritual and moral purification of man and the emergence of divine love. At the same time, it was believed that the incessant creative activity of people, socio-economic changes in society had a unique impact on Sufism, strengthened its syncretism and gave rise to a number of new tarikats, teachings and views.